The classical tradition in Medieval Catalan, 1300-1500 : translation, imitation, and literacy /: translation, imitation, and literacy. (2018) - Cabré, Lluís; Coroleu, Alejandro; Ferrer, Montserrat; Lloret, Albert; Pujol, Josep
No abstract available